Descriptional Time Combinations Described by The Names "Birds and Animals" And "Human Status and Things" In the Turkish Explanatory Dictionary (Eurasian Research Bulletin, 2021)
In Turkish linguistics, the lexeme "time" is not analyzed in terms of semantic layers. Therefore, this article examines the lexical-semantic field of the concept of "time" in Turkish. In the course of research, it has been proved that the phenomenon of meaning transfer can be expressed in different ways in the words that mean "time" in the dictionary.